The Relationship between Brand Image and Brand Trust in Sporting Goods Consumers - Mohammad Deheshti; Javad Adabi Firouzjah; Hossein Alimohammadi (The Society of Aging and Physical Activity (SAPA), 2016)
The image of a brand is the first word or image that is evoked in the mind of costumers immediately after hearing the brand name. The purpose of paying attention to the brand image is to ensure the proper mentality of consumers toward the brand. The components such as suitability, services, brand, variety, quality, and atmosphere form the brand image. The relationship between the brand image and other fields such as brand trust has been considered by researches and can play an effective role in improving the behavioral tendencies of costumers. This study is aimed to examine the relationship between foreign brand image and brand trust among buyers of foreign sports brands. The statistical population of this study consisted of 279 male and female athletes in city of Qom who were buying foreign sports brands. The data collection tool was brand image questionnaire and brand trust questionnaire with Cronbach’s alpha of 0.87 and 0.88, respectively. The results of Pearson’s correlation test showed a significant relationship between image and brand trust (r=0.68). The components of brand image (brand, services, suitability, variety, quality, and atmosphere) with the coefficients of 0.39, 0.53, 0.45, 0.55, 0.51, and 0.54, respectively, had significant correlation with brand trust. The results of simultaneous regression analysis demonstrated that the components of services, variety, quality, and atmosphere could predict the significance of the brand trust among the buyers of foreign sports brands. Based on the results of this study, it seems that the focus on improving the components of services, variety in sale, attention to the quality of products and services, as well as developing a positive atmosphere for customers in providing sale services can have an effective impact on increasing brand trust and improving the behavioral tendencies of costumers.